Analysis of community sports development based on the sports law for development through sports - Muhammad Gilang Ramadhan; Amung Ma'mun; Nuryadi; Tite Juliantine (Journal Sport Area, 2022)
This study aims to examine the implementation of community sports development policies in the context of the "development through sport" paradigm. National development through sports in accordance with the mandate of the Sports Law can be started through community sports which are the basis for the goals of developing the sport itself. This study uses a descriptive qualitative approach. This research was conducted in West Java Province using a purposive sampling technique referring to the high sports achievements achieved at the National Sports Week, but it is still low in the sports development index. Interviews, documentation studies, and observations were carried out in the data collection process. To analyze the data collected, we devised seven indicators that are based on the essence of the sports law of the community sports section. The results of this study found that the implementation of the community sports development policy that was implemented was close to conformity with what was stated in the sports law. However, there are still inequalities in some aspects. This happens because there is still a lack of understanding from the government as policy makers, as well as the community as a group affected by the implementation of policies of the importance of sport as an instrument of national development. Therefore, sports policy makers must act immediately in providing solutions to evaluate policies that will be implemented in the future.